Productivity of mixtures and evolutionary populations of wheat, barley, beans and rice - Mengistu, Dejene Kassahun; Salimi, Maede; Nawal, A.; Neupane, Sumanta; Rinchen, D.; John, M.; Shimelis, Yonas; Nankya, Rose; Jarvis, Devra I. (2023)
Mixtures of different varieties of barley (Hordeum vulgare), wheat (Triticum ssp.) are grown by farmers in Ethiopia, Iran, Jordan, as a means of diversifying production and/or coping with difficult or uncertain growing conditions. Similarly, mixtures of different varieties of beans (Phaseolus vulgaris) were grown by farmers in Bhutan, Nepal and Uganda, with mixtures of Rice (Oryza sativa) were also grown by Bhutan and Nepal farmers. The mixture of all crops in all countries were grown for three consecutive years under IFAD – EPB project. Varietal diversity can improve farmers’ productivity, capabilities to manage pests and diseases and allows farmers to select suitable cultivars in response to varied or uncertain climatic conditions. Moreover, varietal diversification can improve the nutritional security of smallholder farmers.